Association Between the NFKB1-94ins/del ATTG Polymorphism and Cancer Risk: An Updated Meta-Analysis. (9th August 2014) - Duan, Wenyuan; Wang, Erli; Zhang, Fengquan; Wang, Tongjian; You, Xiangdong; Qiao, Bin
Abstract : To assess the effect of the NFKB1 -94ins/del polymorphism on cancer, we conducted a meta-analysis based on 25 studies including 8, 750 cases and 9, 170 controls. Overall, the -94ins/del polymorphism was associated with cancer risk in the pooled analysis and in Asian population, whereas no association was observed in Caucasian population. Stratified analysis by subtypes of cancer showed that the -94ins/del polymorphism was associated with oral squamous cell carcinoma and ovarian cancer risk, but had no association with colorectal cancer, bladder cancer, and renal cell cancer. Our meta-analysis suggests the NFKB1 -94ins/del polymorphism affects cancer susceptibility, and the association is ethnic-specific.